Effect of maternal HIV infection, BMI and NOx air pollution exposure on birth outcomes in South African pregnant women genotyped for the p53 Pro72Arg (rs1042522). (20th February 2020) - Naidoo, Pragalathan; Naidoo, Rajen N.; Ramkaran, Prithiksha; Chuturgoon, Anil A.
Abstract: Tumour suppressor protein, p53, plays a role in modulating innate immune responses, DNA repair, cell cycle arrest, senescence and apoptosis. Maternal nitrogen oxide (NOx) air pollution exposure, body mass index (BMI), human immunodeficiency virus (HIV) infection and p53 Pro72Arg (rs1042522) affect foetal growth. We investigated whether the aforementioned factors influence birth outcomes in a South African population. Pregnant women ( n = 300; HIV −ve = 194 and HIV +ve = 106) were genotyped for the p53 rs1042522 using polymerase chain reaction–restriction fragment length polymorphism (PCR‐RFLP), and further stratified based on HIV status, infants' birthweight (BW; NBW: normal BW [>2, 500 g] and LBW: low BW [<2, 500 g]) and gestational age (GA; NGA: normal GA [>37 weeks] and PTB: preterm birth [≤37 weeks]). A land use regression model was developed to characterize maternal NOx exposure. Pearson's correlation and multivariate regression analysis statistical tests were used to determine the effect of rs1042522 genotyped pregnant women's BMI and NOx exposure on maternal blood pressure and haemoglobin and iron levels, and infants' anthropometric measurements and Appearance Pulse Grimace Activity and Respiration (APGAR) scores. The prevalence of LBW and PTB was 14.7% and 18.7%, respectively. The LBW group had a higher frequency of the variant Arg‐allele versus NBW group (47.7% vs. 31.4%, p = .0046, OR = 2.0, 95% CI = 1.26–3.17). No association was observed between NGA and PTB groups. A significant association between BMI and systolic blood pressure ( r = .50, p = .00; B = 0.76, p = .002) and birth length ( r = −.28, p = .01; B = −0.107, p = .011), and NOx and birth length ( r = −.26, p = .08; B = −0.191, p = .046) and birthweight ( B = −8.87, p = .048) was observed in HIV‐infected mothers with the variant Pro/Arg + Arg/Arg genotypes. Mothers from the LBW group with the variant genotypes displayed an association between NOx and diastolic blood pressure ( r = .58, p = .04), blood iron levels ( r = −.60, p = .04; B = −0.204, p = .004), APGAR scores at 1 min ( r = −.86, p = .00; B = −0.101, p = .003) and 5 min ( r = −.75, p = .01) and birth length ( r = −.61, p = .04), and BMI and diastolic blood pressure ( r = .72, p = .01). In the PTB group, maternal variant genotypes and NOx were associated with blood haemoglobin levels ( B = −0.132, p = .045) and APGAR scores at 1 min ( B = −0.161, p = .045) and 5 min ( B = −0.147, p = .043). Maternal rs1042522 Arg‐allele, HIV infection, BMI and NOx exposure collectively play a role in lowering blood iron levels, gestational hypertension and LBW outcomes.